Identification of Endogenous Surrogate Ligands for Human P2Y Receptors Through an In Silico Search - Takeshi Hiramoto; Yosuke Nonaka; Kazuko Inoue; Takefumi Yamamoto; Mariko Omatsu-Kanbe; Hiroshi Matsuura; Keigo Gohda; Norihisa Fujita (Elsevier, 2004)
G protein-coupled receptors (GPCRs) are distributed widely throughout the human body, and nearly 50% of current medicines act on a GPCR. GPCRs are considered to consist of seven transmembrane α-helices that form an α-helical bundle in which agonists and antagonists bind. A 3D structure of the target GPCR is indispensable for designing novel medicines acting on a GPCR. We have previously constructed the 3D structure of human P2Y1 (hP2Y1) receptor, a GPCR, by homology modeling with the 3D structure of bovine rhodopsin as a template. In the present study, we have employed an in silico screening for compounds that could bind to the hP2Y1-receptor model using AutoDock 3.0. We selected 21 of the 30 top-ranked compounds, and by measuring intracellular Ca2+ concentration, we identified 12 compounds that activated or blocked the hP2Y1 receptor stably expressed in recombinant CHO cells. 5-Phosphoribosyl-1-pyrophosphate (PRPP) was found to activate the hP2Y1 receptor with a low ED50 value of 15 nM. The Ca2+ assays showed it had no significant effect on P2Y2, P2Y6, or P2X2 receptors, but acted as a weak agonist on the P2Y12 receptor. This is the first study to rationally identify surrogate ligands for the P2Y-receptor family. Keywords:: G protein-coupled receptor, P2Y1 receptor, in silico screening, AutoDock, 5-phosphoribosyl-1-pyrophosphate